Human Biomonitoring in the Oil Shale Industry Area in Estonia—Overview of Earlier Programmes and Future Perspectives - Orru, Hans; Viitak, Anu; Herodes, Koit; Veber, Triin; Lukk, Märten (Frontiers in Public Health, 2020)
Ida-Viru County, in Eastern Estonia, features industrially contaminated sites– where oil shale has been mined and used for electricity generation, and shale oil extraction. Higher prevalence of respiratory and cardiovascular disease has been found in the region due to high quantities of air pollution. Within the framework of “Studies of the health impact of the oil shale sector—SOHOS,” this analysis aimed to map earlier human biomonitoring (HBM) studies and identify the suitable biomarkers for upcoming HBM in Estonia. Altogether, three studies were conducted among residents: first, among adults in the 1980s; second, among children in the 1990s; and third, among employees, with a focus on workers and miners in the oil shale chemistry industry in the late 1990s and 2000s. In some of those studies, increased levels of biomarkers in blood and urine (heavy metals, 1-OHP) appeared; nevertheless, in last 20 years, there has been no population-wide HBM in Estonia. According to air pollution monitoring and emission analysis, the pollutants of concern are benzene, PM10, PM2.5, and PAHs. In general, there is a decreasing trend in air pollutant levels, with the exception of a slight increase in 2018. One of the aims of HBM is to be analysed if this trend can be identified in HBM, using similar biomarkers as applied earlier. The future perspective HBM could be divided into two Tiers. Tier 1 should focus on exposure biomarkers as heavy metals, PAH, and BTEX metabolites and Tier 2, in later stage, on effect biomarkers as Ox LDL, TBARS, etc.